The Use of Arctic Science: POPs, Norway and the Stockholm Convention - Rottem, Svein Vigeland (Arctic Review on Law and Politics, 2017)
The Use of Arctic Science: POPs, the Stockholm Convention and Norway The focus in this article is on how scientific knowledge on POPs in the Arctic has been used in international regulations, and can be used today. More specifically, I explore Norway’s active (and successful) nominations over the past decade of new POPs to the Stockholm Convention, nominations that need a scientific knowledge basis, and where Arctic scientific knowledge has been a prerequisite for action. The article will first discuss the Stockholm Convention`s relation to other legal instruments on regulating POPs, and provide an introduction to how the Convention works. However, to obtain a more complete picture of how science travels into global governance we need to bring the State in. We need to know how scientific knowledge is used (or not used) at the national level. The question guiding the second part of this study is what has determined the use of scientific knowledge in Norwegian efforts leading to the nomination of new POPs to the Stockholm Convention. The focus is on environmental management design, state of knowledge, degree of political and economic controversy in the issue area, and the importance of the matter in public opinion and among policy makers. The conclusion is that Norway has had little to lose by initiating work on regulating new POPs and being active in the nomination of new POPs. Being green (or using scientific knowledge) in this case has been scientifically demanding, but politically easy.